Writers and Their Mothers (Springer International Publishing, 2018)
Ian McEwan, Margaret Drabble, Martin Amis, Rita Dove, Andrew Motion and Anthony Thwaite are among the twenty-two distinguished contributors of original essays to this landmark volume on the profound and frequently perplexing bond between writer and mother. In compelling detail they bring to life the thoughts, work, loves, friendships, passions and, above all, the influence of mothers upon their literary offspring from Shakespeare to the present. Many of the contributors evoke the ideal with fond and loving memories: understanding, selfless, spiritual, tender, protective, reassuring and self-assured mothers who created environments favorable to the development of their children's gifts. At the opposite end of the parenting spectrum, however, we also see tortured mothers who ignored, interfered with, smothered or abandoned their children. Their early years were times of traumatic loss, unhappily dominated by death and human frailty. Elegantly assembled and presented, Writers and Their Mothers will appeal to everyone interested in biography, literature, and creativity in general.